A Rare Case of Placental Abruption Along With Couvelaire Uterus And Uterine Scar Rupture: A Case Report - Shahid, Wania; Khalid, Amna; Chaudhry, Shama (Journal of Rawalpindi Medical College, 2024)
Placental abruption (PA), is defined as the detachment of the placenta, partially or fully, from the wall of the uterus before delivery. Severe PA could lead to a couvelarie uterus (CU), a rare but intricate complication. This report discusses the case of a 25-year-old female not only with placental abruption and couvelaire uterus but also with uterine scar rupture, further complicating the matter. This report aims to help reduce morbidity and mortality in such cases, emphasising timely recognition, intervention and swift treatment to achieve favourable outcomes.